THE EFFECT OF OVAPRIM INJECTION WITH DIFFERENT DOSES ON OVULATIONEGGS OF KAPIU (Barbodes lateristriga Val.1842) - Intan Nuraysah; Nuraini Nuraini; Sukendi Sukendi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractThis research was conducted from January to February 2019 at the Laboratory of Fish Hatchery and Breeding at the Faculty of Fisheries and Marine Sciences, University of Riau. This study aims to determine the effect of ovaprim to ovulation and hatching rate of  kapiu. The treatment in this study was P0  : injection of NaCL (0,9 %) 0,1ml/kg body weight, P1 : injection of ovaprim 0,5ml/kg body weight, P2: injection of ovaprim 0,7ml/kg body weight and P3: injection of ovaprim 0,9ml/kg body weight.The best result of the research isinjection of ovaprim  with dose 0,7ml/kg body weight of kapiu (Barbodes lateristriga) with latent time 8 hours and 10 minutes, and oviposition of 34 ±7.83 item/g female spawner. The water quality parameter during the study the temperature range from 27-29°C, pH was 5-6 dan DO 5,2-6,6 ppm. Keywords : Ovaprim, Ovulation, Survival rate, Barbodes lateristriga